Immobilized lipase based on carboxymethyl chitosan / lignin cross-linked composite microspheres as well as preparation and application of immobilized lipase
The carboxymethyl chitosan/lignin crosslinking composite microspheres prepared by crosslinking lignin with carboxymethyl chitosan solved the poor mechanical properties of the immobilized enzyme carrier and the lignin sulfonate ease. The problem is that high enzyme loading volume, activity and stability have been achieved, and the industrial application prospects of enzymes have been enhanced.
Patent Information
- Application Number
- CN202411421012.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-07
AI Technical Summary
Existing immobilized enzyme carriers such as pure chitosan and pure carboxymethyl chitosan microspheres have problems of poor mechanical properties and easy to break, which limits the industrial application of immobilized enzymes, and when lignin sulfonate is used in water Easy to exudate, affecting stability.
The amino coupling agent EDC/NHS is used to modify lignin to form cross-linked with carboxymethyl chitosan, and prepare a composite microsphere based on carboxymethyl chitosan/lignin to realize lipase In situ embedding and stable immobilization of enzymes, the hydrophobicity of lignin is used to activate enzyme activity.
It improves the enzyme loading, catalytic activity and the mechanical properties of the microspheres, ensures the stability and efficient recycling of the enzyme, avoids the exudation of lignin sulfonate, and enhances the reusability of the microspheres.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of immobilized lipase preparation, and in particular relates to immobilized lipase based on carboxymethyl chitosan / lignin cross-linked composite microspheres and preparation and application thereof. Background Art
[0002] Lipase is one of the most widely used enzymes due to its wide sources and specific catalytic activity. In addition to its biological functions in bacteria, fungi, plants and higher animals, it has attracted extensive attention as a biocatalyst in industries such as oil processing, food processing, leather, textiles, detergents, papermaking, fine chemical synthesis, pharmaceuticals, and cosmetics. However, free lipase is easily inactivated by external factors such as temperature and pH value, and is difficult to recycle and reuse. Immobilized enzyme technology can effectively solve the above problems. Immobilized lipase has both the catalytic properties of enzymes and the advantages of general chemical catalysts such as recyclability and repeated use. Its development and utilization has broad application prospects.
[0003] The performance of immobilized lipase is closely related to the carrier. Chitosan has good biocompatibility and biodegradability, is green, safe, non-toxic, and environmentally friendly, and is a commonly used immobilized enzyme carrier. Klein et al. (Carbohyd Polym, 2016, 137: 184-190) used non-toxic genipin as a cross-linking agent to prepare activated chitosan particles to immobilize β-galactosidase. By optimizing the initial lactose concentration, pH value and temperature, the yield of galactose prepared by the immobilized enzyme was 30%. Wang et al. (European Food Research and Technology, 2014, 239(6): 1051-1059) used chitosan to coat magnetic nanoparticles and used glutaraldehyde as a cross-linking agent to activate the carrier to immobilize alkaline protease. The optimal temperature and pH range of the immobilized enzyme were significantly increased compared with the free enzyme. The enzymatic hydrolysis of soy protein isolate was 140 min, and the degree of hydrolysis was 18.38%, which was higher than the 17.50% of the free enzyme. Monteiro et al. (Monteiro CRR, Lima MJP, Pinheiro BB, et al. Immobilization of Lipase A from Candida antarctica onto Chitosan-Coated Magnetic Nanoparticles [J]. International Journal of Molecular Sciences, 2019, 20 (16): 4018.) prepared chitosan microspheres and used the crosslinking agent glutaraldehyde to covalently link the chitosan microspheres and lipase. The maximum enzyme loading was 84 mg / g, and 48% of the enzyme activity remained after 8 cycles. Although chitosan has a good immobilization effect on different biological enzymes, chitosan is insoluble in water and is only soluble in weak acid solutions with a pH value below 6.5. Therefore, when chitosan is used to immobilize lipase, it is necessary to first prepare a chitosan carrier and then load the lipase by adsorption, resulting in a low enzyme loading. Carboxymethyl chitosan has better water solubility, and lipase can be embedded in carboxymethyl chitosan microspheres by in situ embedding to increase the enzyme loading. However, pure chitosan microspheres and pure carboxymethyl chitosan microspheres have the disadvantages of poor mechanical properties and easy breakage, which seriously limits the industrial application of immobilized enzymes. They need to be compounded with other reinforcing materials to improve the mechanical properties of the microspheres, thereby improving the durability of the immobilized enzymes.
[0004] In addition, during the lipase immobilization process, the interaction between the hydrophobic carrier material and the enzyme has an activation effect on the lipase. This is because the active site of the free lipase is covered by a hydrophobic oligopeptide (commonly referred to as a "lid"), which hinders the contact between the active site and the substrate; when there is a hydrophobic carrier interface, the interaction opens the lid of the lipase, and the active site changes from a closed form to an open form, thereby increasing the catalytic enzyme activity. Therefore, the interfacial adsorption of lipase on a hydrophobic carrier is a common method for preparing immobilized lipase with high catalytic activity.
[0005] Lignin is the second largest biomass resource in nature. It is a three-dimensional network structure natural polymer composed of phenylpropane units and is hydrophobic. According to the catalytic mechanism of lipase, the hydrophobicity of lignin can significantly improve the catalytic activity of lipase through interfacial activation. Zhang et al. (Industrial Crops and Products, 2023, 193:116241) used lignin from corncob residue as a carrier to immobilize Antarctic Candida albicans lipase B, which enhanced the hydrophobic interaction between the carrier and the lipase, so that the immobilized enzyme still maintained 77.0% of its activity after 20 days of storage, and maintained 88.6% of its initial activity after 5 cycles of use. Park et al. (Carbohydrate Polymers, 2015, 115:223–229) immobilized Candida albicans lipase on cellulose / lignin microbeads. Compared with single cellulose, the addition of lignin significantly improved the stability and activity of the immobilized enzyme. On the other hand, as a biopolymer with a rigid structure, lignin can form a cross-linked network with hydrogels that can significantly improve the mechanical strength of hydrogels. For example, Gregorich et al. (ACS Applied Polymer Materials, American Chemical Society, 2023, 5(1):201–213) synthesized polyvinyl alcohol / lignin hydrogel composites and found that the addition of lignin significantly improved the mechanical properties of the composites, with the storage modulus significantly increased to 860% of the original value. Therefore, lignin can both improve the catalytic activity of lipase and enhance the mechanical properties of the gel. Combining lignin with carboxymethyl chitosan may be an effective way to enhance the mechanical properties of carboxymethyl chitosan microspheres, improve the catalytic activity of lipase, and prepare a fully bio-based enzyme immobilization carrier.
[0006] Industrial lignin is mainly composed of alkali lignin, enzymatic lignin and lignin sulfonate. Alkali lignin and enzymatic lignin contain a large number of functional groups, such as hydroxyl, phenyl, methoxy, ether bond, carboxyl, etc., but they have low molecular weight and poor water solubility, and can only be dissolved in alkaline media, which limits their application to a certain extent. Lignin sulfonate has very good hydrophilicity and can be dissolved in water with carboxymethyl chitosan and lipase to form a mixed solution to achieve in-situ embedding of the enzyme, but lignin sulfonate is very easy to seep out when the immobilized enzyme is used in water. Therefore, it is urgent to develop a new technology for preparing immobilized lipase with high stability by compounding carboxymethyl chitosan and lignin. Summary of the invention
[0007] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing immobilized lipase based on carboxymethyl chitosan / lignin cross-linked composite microspheres.
[0008] The present invention uses amino coupling agent EDC / NHS (EDC is 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide, NHS is N-hydroxysuccinimide) to modify lignin and prepare immobilized enzyme. First, the modified lignin is obtained by amination and carboxylation of lignin, then the carboxymethyl chitosan, the modified lignin and the lipase are mixed with an aqueous solution to form an oil-in-water emulsion, and finally EDC / NHS is used to simultaneously cross-link the carboxymethyl chitosan, the modified lignin and the lipase to achieve microsphere preparation and enzyme immobilization. The modified lignin has good water solubility and can achieve in-situ encapsulation of the lipase. After cross-linking into a ball, it will not seep out during use, and the hydrophobicity of the benzene ring helps to stimulate the catalytic activity of the lipase.
[0009] Another object of the present invention is to provide an immobilized lipase with high enzyme loading, catalytic activity and good mechanical properties obtained by the above preparation method.
[0010] Another object of the present invention is to provide the application of the immobilized lipase based on the carboxymethyl chitosan / lignin cross-linked composite microspheres.
[0011] The purpose of the present invention is achieved through the following technical solutions: A method for preparing immobilized lipase based on carboxymethyl chitosan / lignin cross-linked composite microspheres comprises the following steps: (1) dissolving lignin in an alkaline solution, adding formaldehyde and an amination modifier to carry out an amination reaction to obtain aminated lignin; then adding an amino coupling agent and a carboxylation modifier to carry out a carboxylation reaction, dialyzing, and drying to obtain aminated-carboxylation modified lignin; (2) mixing carboxymethyl chitosan, aminated-carboxylated modified lignin, lipase and water to obtain an aqueous phase solution; mixing the aqueous phase solution and an oil phase containing a surfactant, emulsifying, and obtaining a W / O emulsion; (3) Adding an amino coupling agent solution dropwise to the W / O emulsion to undergo a cross-linking reaction at room temperature, allowing the emulsion to stand for stratification, removing the lower layer, washing it, and filtering it to obtain immobilized lipase based on carboxymethyl chitosan / lignin cross-linked composite microspheres.
[0012] Preferably, the lignin in step (1) is at least one of alkali lignin, enzymatic lignin and lignin sulfonate; more preferably, it is at least one of alkali lignin, enzymatic lignin and sodium lignin sulfonate; most preferably, it is alkali lignin.
[0013] Preferably, the alkaline solution in step (1) is at least one of a sodium hydroxide solution and a potassium hydroxide solution, and the concentration of the alkaline solution is 1.0 to 4.0 mol / L; the concentration of the lignin in the alkaline solution is 20 to 60 wt%; further preferably, the concentration of the alkaline solution is 2 to 4.0 mol / L; the concentration of the lignin in the alkaline solution is 20 to 50 wt%.
[0014] Preferably, in step (1), the mass ratio of lignin, formaldehyde and aminated modifier is 1: (0.37-1.11): (0.2-1.0); further preferably, the mass ratio of lignin, formaldehyde and aminated modifier is 1: (0.555-1.11): (0.2-1.0).
[0015] Preferably, the formaldehyde in step (1) is added in the form of a formaldehyde solution, and the concentration of the formaldehyde solution is 30-40 wt %, more preferably 37 wt %.
[0016] Preferably, the amination modifier in step (1) is at least one of ethylenediamine, diethylenetriamine, triethylenetetramine and tetraethylenepentamine; more preferably at least one of ethylenediamine and tetraethylenepentamine.
[0017] Preferably, the temperature of the amination reaction in step (1) is 60-90°C, and the reaction time is 1-4 h; further preferably, the temperature of the amination reaction is 70-80°C, and the reaction time is 1-2 h.
[0018] Preferably, the amino coupling agent in step (1) is EDC / NHS (EDC is 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide, and NHS is N-hydroxysuccinimide).
[0019] Preferably, the carboxyl modifier in step (1) is at least one of ethylenediaminetetraacetic acid and diethylenetriaminepentaacetic acid; more preferably, it is ethylenediaminetetraacetic acid.
[0020] Preferably, in step (1), the mass ratio of the lignin, the amino coupling agent and the carboxyl modifier is 1: (0.12-0.8): (0.5-2.0); the amino coupling agent is EDC / NHS, the amount of EDC is 100-400 mg / g lignin, the amount of NHS is 0.2-1.0 mg / mg EDC, and the mass ratio of the lignin to the carboxyl modifier is 1: (0.5-2.0); further preferably, the mass ratio of the lignin, the amino coupling agent and the carboxyl modifier is 1: (0.15-0.2): (0.5-2.0); the amount of EDC is 100-300 mg / g lignin, the amount of NHS is 0.5-1.0 mg / mg EDC; the mass ratio of the lignin to the carboxyl modifier is 1: 0.5.
[0021] Preferably, the temperature of the carboxylation reaction in step (1) is 30-40°C, and the time is 12-36 h; further preferably, the temperature of the carboxylation reaction is 30°C, and the time is 24 h.
[0022] Preferably, the dialysis in step (1) refers to dialysis using a 1000 Da dialysis bag at room temperature for 5 days.
[0023] Preferably, the drying in step (1) is freeze-drying.
[0024] Preferably, in step (2), the mass of the carboxymethyl chitosan accounts for 3.0-9.0 wt% of the aqueous solution; the mass of the aminated-carboxylated modified lignin accounts for 0.5-9.0 wt% of the aqueous solution; further preferably, the mass of the carboxymethyl chitosan accounts for 3.0-6.0 wt% of the aqueous solution; the mass of the aminated-carboxylated modified lignin accounts for 0.5-5.0 wt% of the aqueous solution.
[0025] Preferably, the lipase in step (2) is at least one of Candida rugosa lipase, Aspergillus niger lipase and Candida albicans lipase; the amount of the lipase is 0.05-0.8 g / g carboxymethyl chitosan; further preferably, the amount of the lipase is 0.4-0.6 g / g carboxymethyl chitosan.
[0026] Preferably, in the surfactant-containing oil phase in step (2), the surfactant content is 0.5 to 3.0 wt %; more preferably, the surfactant content is 1.0 to 2.0 wt %.
[0027] Preferably, the surfactant-containing oil phase in step (2) is at least one of liquid paraffin, ethyl acetate, dodecane and soybean oil; more preferably at least one of liquid paraffin and soybean oil.
[0028] Preferably, in the surfactant-containing oil phase of step (2), the surfactant is at least one of Span-80, Span-60, sucrose ester, Tween-80, sodium dodecyl sulfate and sodium dodecylbenzene sulfonate; more preferably at least one of Span-80 and Tween-80.
[0029] Preferably, in step (2), the mass ratio of the aqueous solution to the oil phase containing a surfactant is 1:2 to 1:10; further preferably, the mass ratio of the aqueous solution to the oil phase is 1:8 to 1:10.
[0030] Preferably, the emulsification speed in step (2) is 100-800 rpm, and the time is 10-120 min; further preferably, the emulsification speed is 500-600 rpm, and the time is 30-120 min.
[0031] Preferably, the amino coupling agent in the amino coupling agent solution of step (3) is EDC / NHS; the amount of the amino coupling agent solution is 10-30 wt% of the aqueous solution; the EDC concentration in the amino coupling agent solution is 2.5-25 wt%; and the amount of NHS is 0.2-1.0 mg / mg EDC; further preferably, the amount of the amino coupling agent solution is 20 wt% of the aqueous solution; the EDC concentration in the amino coupling agent solution is 2.5-25 wt%; and the amount of NHS is 0.5-0.8 mg / mg EDC.
[0032] Preferably, the cross-linking reaction time in step (3) is 1 to 6 h; more preferably, it is 2 to 3 h.
[0033] Preferably, the standing and stratifying time in step (3) is 5 to 30 min; more preferably, it is 10 min.
[0034] Preferably, the washing and filtering in step (3) are as follows: adding a mixture of water and petroleum ether for washing 3 to 6 times, wherein the volume ratio of water to petroleum ether is 1:1 to 5:1, and then transferring the composite microsphere immobilized lipase to a Buchner funnel and vacuum filtering for 10 to 30 minutes.
[0035] The preparation method mentioned above obtains an immobilized lipase based on carboxymethyl chitosan / lignin cross-linked composite microspheres.
[0036] The particle size of the carboxymethyl chitosan / lignin cross-linked composite microspheres for immobilizing lipase prepared by the invention is 100-800 μm.
[0037] The above-mentioned application of immobilized lipase based on carboxymethyl chitosan / lignin cross-linked composite microspheres.
[0038] The carboxymethyl chitosan / lignin cross-linked composite microspheres of immobilized lipase prepared by the invention are used as biocatalysts.
[0039] Preferably, the carboxymethyl chitosan / lignin cross-linked composite microspheres of immobilized lipase are used as biocatalysts in the preparation of foods, medicines, and detergents.
[0040] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. The composite microspheres prepared by the present invention have a high enzyme loading capacity. Lipase, carboxymethyl chitosan and modified lignin are cross-linked to form composite microspheres, and the lipase is in situ embedded in the composite microspheres. The enzyme loading capacity is high, and the lipase is firmly combined with the carrier, has good stability, and is not easy to fall off from the microspheres.
[0041] 2. The microspheres prepared by the present invention have good mechanical properties. The modified lignin with high amino and carboxyl content and carboxymethyl chitosan are cross-linked with each other using EDC / NHS to form an interlaced network structure, thereby enhancing the mechanical properties of the composite microspheres and improving the reusability of the microspheres.
[0042] 3. The enzyme-loaded composite microspheres prepared by the present invention have good catalytic performance. The hydrophobicity of lignin is conducive to opening the "lid" covering the active center of lipase, which has a positive effect on improving the catalytic performance of lipase.
[0043] 4. The particle size of the microspheres prepared by the present invention is controllable. The particle size of the composite microspheres can be adjusted from 100 to 800 μm by changing the oil-water ratio, using surfactants of different masses and emulsion shear rates. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 The infrared spectra of the alkali lignin and modified lignin prepared in Example 1.
[0045] Figure 2 This is a scanning electron micrograph of the overall appearance of the immobilized lipase based on carboxymethyl chitosan / lignin cross-linked composite microspheres prepared in Example 1.
[0046] Figure 3 This is a cross-sectional scanning electron micrograph of the immobilized lipase based on carboxymethyl chitosan / lignin cross-linked composite microspheres prepared in Example 1.
[0047] Figure 4 This is a laser confocal image of the immobilized lipase based on carboxymethyl chitosan / lignin cross-linked composite microspheres prepared in Example 1.
[0048] Figure 5 This is a contact angle measurement image of the immobilized lipase based on carboxymethyl chitosan / lignin cross-linked composite microspheres prepared in Example 1.
[0049] Figure 6 The mechanical properties and enzyme activity of the immobilized lipase obtained in Examples 1 to 7 and Comparative Examples 1 to 3.
[0050] Figure 7 This is the turbidity graph of the stirred suspension of immobilized lipase based on carboxymethyl chitosan / lignin cross-linked composite microspheres prepared in Example 1.
[0051] Figure 8 This is the reusability of the immobilized lipase based on carboxymethyl chitosan / lignin cross-linked composite microspheres prepared in Example 1. DETAILED DESCRIPTION
[0052] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0053] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.
[0054] Example 1 (1) Preparation of modified lignin: 2.0 g of alkali lignin was dissolved in 4.0 mol / L sodium hydroxide solution to prepare 10 g of 20 wt% alkali lignin solution; 6.0 g of 37 wt% formaldehyde aqueous solution and 2.0 g of ethylenediamine were added under stirring, mixed evenly and heated to 80 °C for reaction for 1 h to obtain an aminated alkali lignin solution; after cooling, 600 mg of EDC, 600 mg of NHS and 1.0 g of ethylenediaminetetraacetic acid were added, stirred and reacted at 30 °C for 24 h, the reaction solution was poured into a dialysis bag (1000 Da) and dialyzed for 5 days, and freeze-dried to obtain an aminated-carboxylated modified lignin powder.
[0055] (2) Preparation of W / O emulsion: 0.05 g of modified lignin, 0.3 g of carboxymethyl chitosan and 0.12 g of Candida rugosa lipase obtained in step (1) were dissolved in deionized water to prepare 10 g of aqueous solution; the aqueous solution was added to 100 g of liquid paraffin containing 1.0 wt% Span-80 and emulsified at 500 rpm for 30 min using mechanical stirring.
[0056] (3) Preparation of immobilized lipase: 2.0 g of a crosslinker solution containing 50 mg EDC and 25 mg NHS was added dropwise to the W / O emulsion obtained in step (2), and the mixture was stirred and crosslinked at room temperature for 2 h. After the reaction was completed, the mixture was allowed to stand for 10 min to separate the layers, and the upper oil phase was poured out, and 200 ml of a mixed solution containing 100 ml deionized water and 100 ml petroleum ether was poured in to wash three times, and then the mixture was transferred to a Buchner funnel and vacuum filtered for 10 min to obtain immobilized lipase based on carboxymethyl chitosan / lignin crosslinked composite microspheres.
[0057] Example 2 (1) Preparation of modified lignin: 3.0 g of enzymatically hydrolyzed lignin was dissolved in 1.0 mol / L potassium hydroxide solution to prepare 10 g of 30 wt% enzymatically hydrolyzed lignin solution; 7.5 g of 37 wt% formaldehyde aqueous solution and 2.4 g of diethylenetriamine were added under stirring, mixed evenly, and the mixture was heated to 60 °C and reacted for 3 h to obtain an aminated alkali lignin solution; after cooling, 600 mg of EDC, 300 mg of NHS and 3.0 g of diethylenetriamine pentaacetic acid were added, and the mixture was stirred and reacted at 40 °C for 12 h. The reaction solution was poured into a dialysis bag (1000 Da) and dialyzed for 5 days. The solution was freeze-dried to obtain an aminated-carboxylated modified lignin powder.
[0058] (2) Preparation of W / O emulsion: 0.1 g of modified lignin, 0.9 g of carboxymethyl chitosan and 0.045 g of Aspergillus niger lipase obtained in step (1) were dissolved in deionized water to prepare 10 g of aqueous solution; the aqueous solution was added to 20 g of ethyl acetate containing 0.5 wt% Span-60 and emulsified at 100 rpm for 10 min using magnetic stirring.
[0059] (3) Preparation of immobilized lipase: 2.0 g of a crosslinker solution containing 90 mg EDC and 36 mg NHS was added dropwise to the W / O emulsion obtained in step (2), and the mixture was stirred and crosslinked at room temperature for 4 h. After the reaction was completed, the mixture was allowed to stand for 10 min to separate the layers, and the upper oil phase was poured out, and a 200 ml mixed solution containing 150 ml deionized water and 50 ml petroleum ether was poured in to wash 4 times, and then the mixture was transferred to a Buchner funnel and vacuum filtered for 20 min to obtain immobilized lipase based on carboxymethyl chitosan / lignin crosslinked composite microspheres.
[0060] Example 3 (1) Preparation of modified lignin: 4.0 g of sodium lignin sulfonate was dissolved in 4.0 mol / L potassium hydroxide solution to prepare 10 g of 40 wt% sodium lignin sulfonate solution; 8.0 g of 37 wt% formaldehyde aqueous solution and 2.0 g of triethylenetetramine were added under stirring, mixed evenly and heated to 90 °C for 4 h to obtain an aminated alkali lignin solution; after cooling, 1600 mg of EDC, 320 mg of NHS and 8.0 g of ethylenediaminetetraacetic acid were added, stirred and reacted at 30 °C for 12 h, the reaction solution was poured into a dialysis bag (1000 Da) and dialyzed for 5 days, and freeze-dried to obtain an aminated-carboxylated modified lignin powder.
[0061] (2) Preparation of W / O emulsion: 0.3 g of modified lignin, 0.5 g of carboxymethyl chitosan and 0.4 g of Candida albicans lipase obtained in step (1) were dissolved in deionized water to prepare 10 g of aqueous solution; the aqueous solution was added to 50 g of dodecane containing 3.0 wt% sucrose ester and emulsified at 800 rpm for 60 min using magnetic stirring.
[0062] (3) Preparation of immobilized lipase: 2.0 g of a crosslinker solution containing 400 mg EDC and 400 mg NHS was added dropwise to the W / O emulsion obtained in step (2), and the mixture was stirred and crosslinked for 6 h at room temperature. After the reaction was completed, the mixture was allowed to stand for 10 min to separate the layers, and the upper oil phase was poured out, and a 200 ml mixed solution containing 160 ml deionized water and 40 ml petroleum ether was poured in to wash 6 times, and then the mixture was transferred to a Buchner funnel and vacuum filtered for 15 min to obtain immobilized lipase based on carboxymethyl chitosan / lignin crosslinked composite microspheres.
[0063] Example 4 (1) Preparation of modified lignin: 5.0 g of sodium lignin sulfonate was dissolved in 2.0 mol / L sodium hydroxide solution to prepare 10 g of 50 wt% sodium lignin sulfonate solution; 7.5 g of 37 wt% formaldehyde aqueous solution and 1.0 g of tetraethylenepentamine were added under stirring, mixed evenly and heated to 70 °C for 2 h to obtain an aminated alkali lignin solution; after cooling, 500 mg of EDC, 250 mg of NHS and 10.0 g of ethylenediaminetetraacetic acid were added, stirred and reacted at 40 °C for 36 h, the reaction solution was poured into a dialysis bag (1000 Da) and dialyzed for 5 days, and freeze-dried to obtain an aminated-carboxylated modified lignin powder.
[0064] (2) Preparation of W / O emulsion: 0.5 g of modified lignin, 0.6 g of carboxymethyl chitosan and 0.36 g of Candida albicans lipase obtained in step (1) were dissolved in deionized water to prepare 10 g of aqueous solution; the aqueous solution was added to 80 g of soybean oil containing 2.0 wt% Tween-80 and emulsified at 600 rpm for 120 min using mechanical stirring.
[0065] (3) Preparation of immobilized lipase: 2.0 g of a crosslinker solution containing 500 mg EDC and 400 mg NHS was added dropwise to the W / O emulsion obtained in step (2), and the mixture was stirred and crosslinked at room temperature for 3 h. After the reaction was completed, the mixture was allowed to stand for 10 min to separate the layers, and the upper oil phase was poured out, and a 200 ml mixed solution containing 120 ml deionized water and 80 ml petroleum ether was poured in to wash 5 times, and then the mixture was transferred to a Buchner funnel and vacuum filtered for 30 min to obtain immobilized lipase based on carboxymethyl chitosan / lignin crosslinked composite microspheres.
[0066] Example 5 (1) Preparation of modified lignin: 6.0 g of enzymatically hydrolyzed lignin was dissolved in 3.0 mol / L sodium hydroxide solution to prepare 10 g of 60 wt% enzymatically hydrolyzed lignin solution; 6.0 g of 37 wt% formaldehyde aqueous solution and 3.0 g of triethylenetetramine were added under stirring, mixed evenly and heated to 60 °C for reaction for 1 h to obtain an aminated alkali lignin solution; after cooling, 1200 mg of EDC, 720 mg of NHS and 6.0 g of diethylenetriaminepentaacetic acid were added, stirred and reacted at 40 °C for 24 h, the reaction solution was poured into a dialysis bag (1000 Da) and dialyzed for 5 days, and freeze-dried to obtain an aminated-carboxylated modified lignin powder.
[0067] (2) Preparation of W / O emulsion: 0.9 g of modified lignin, 0.9 g of carboxymethyl chitosan, and 0.18 g of Candida rugosa lipase obtained in step (1) were dissolved in deionized water to prepare 10 g of aqueous solution; the aqueous solution was added to 30 g of ethyl acetate containing 2.0 wt% sodium dodecyl sulfate, and emulsified at 400 rpm for 100 min using magnetic stirring.
[0068] (3) Preparation of immobilized lipase: 2.0 g of a crosslinker solution containing 180 mg EDC and 108 mg NHS was added dropwise to the W / O emulsion obtained in step (2), and the mixture was stirred and crosslinked at room temperature for 1 h. After the reaction was completed, the mixture was allowed to stand for 10 min to separate the layers, and the upper oil phase was poured out, and a 200 ml mixed solution containing 130 ml deionized water and 70 ml petroleum ether was poured in to wash 5 times, and then the mixture was transferred to a Buchner funnel and vacuum filtered for 30 min to obtain immobilized lipase based on carboxymethyl chitosan / lignin crosslinked composite microspheres.
[0069] Example 6 (1) Preparation of modified lignin: 6.0 g of alkali lignin was dissolved in 1.0 mol / L sodium hydroxide solution to prepare 10 g of 60 wt% alkali lignin solution; 18.0 g of 37 wt% formaldehyde aqueous solution and 6.0 g of diethylenetriamine were added under stirring, mixed evenly and heated to 90 °C for reaction for 2 h to obtain an aminated alkali lignin solution; after cooling, 600 mg of EDC, 120 mg of NHS and 9.0 g of ethylenediaminetetraacetic acid were added, stirred and reacted at 30 °C for 36 h, the reaction solution was poured into a dialysis bag (1000 Da) and dialyzed for 5 days, and freeze-dried to obtain an aminated-carboxylated modified lignin powder.
[0070] (2) Preparation of W / O emulsion: 0.7 g of modified lignin, 0.8 g of carboxymethyl chitosan and 0.4 g of Candida albicans lipase obtained in step (1) were dissolved in deionized water to prepare 10 g of aqueous solution; the aqueous solution was added to 40 g of liquid paraffin containing 1.5 wt% sodium dodecylbenzene sulfate and emulsified at 500 rpm for 50 min using magnetic stirring.
[0071] (3) Preparation of immobilized lipase: 2.0 g of a crosslinker solution containing 240 mg EDC and 120 mg NHS was added dropwise to the W / O emulsion obtained in step (2), and the mixture was stirred and crosslinked at room temperature for 5 h. After the reaction was completed, the mixture was allowed to stand for 10 min to separate the layers, and the upper oil phase was poured out, and a 200 ml mixed solution containing 160 ml deionized water and 40 ml petroleum ether was poured in to wash three times, and then the mixture was transferred to a Buchner funnel and vacuum filtered for 20 min to obtain immobilized lipase based on carboxymethyl chitosan / lignin crosslinked composite microspheres.
[0072] Example 7 (1) Preparation of modified lignin: 4.0 g of enzymatically hydrolyzed lignin was dissolved in 3.0 mol / L potassium hydroxide solution to prepare 10 g of 40 wt% enzymatically hydrolyzed lignin solution; 8.0 g of 37 wt% formaldehyde aqueous solution and 0.8 g of tetraethylenepentamine were added under stirring, mixed evenly, and the mixture was heated to 70 °C and reacted for 1 h to obtain an aminated alkali lignin solution; after cooling, 800 mg of EDC, 800 mg of NHS and 2.0 g of diethylenetriaminepentaacetic acid were added, and the mixture was stirred and reacted at 40 °C for 36 h. The reaction solution was poured into a dialysis bag (1000 Da) and dialyzed for 5 days, and freeze-dried to obtain an aminated-carboxylated modified lignin powder.
[0073] (2) Preparation of W / O emulsion: 0.2 g of modified lignin obtained in step (1), 0.4 g of carboxymethyl chitosan, and 0.28 g of Aspergillus niger lipase were dissolved in deionized water to prepare 10 g of aqueous solution; the aqueous solution was added to 70 g of dodecane containing 3.0 wt% Span-60, and emulsified at 200 rpm for 80 min using mechanical stirring.
[0074] (3) Preparation of immobilized lipase: 2.0 g of a crosslinker solution containing 200 mg EDC and 40 mg NHS was added dropwise to the W / O emulsion obtained in step (2), and the mixture was stirred and crosslinked for 3 h at room temperature. After the reaction was completed, the mixture was allowed to stand for 10 min to separate the layers, and the upper oil phase was poured out, and a 200 ml mixed solution containing 110 ml deionized water and 90 ml petroleum ether was poured in and washed 6 times, and then the mixture was transferred to a Buchner funnel and vacuum filtered for 15 min to obtain immobilized lipase based on carboxymethyl chitosan / lignin crosslinked composite microspheres.
[0075] Comparative Example 1 In order to compare the effect of lignin on the hydrophobicity, mechanical properties and enzyme activity of immobilized enzyme, immobilized lipase based on pure carboxymethyl chitosan microspheres was prepared without adding lignin, with reference to Example 1: 0.3g carboxymethyl chitosan and 0.12g Candida rugosa lipase were dissolved in deionized water to prepare 10g aqueous solution; the aqueous solution was added to 100g liquid paraffin containing 1.0wt% Span-80, and mechanical stirring was used for emulsification at 500rpm for 30 min. 2.0g of crosslinker solution containing 50mg EDC and 25mg NHS was added dropwise to the obtained W / O emulsion, and stirred for crosslinking for 2h. After the reaction was completed, it was allowed to stand for 10min to separate layers, and the upper oil phase was poured out, and 200ml of a mixed solution containing 100ml deionized water and 100ml petroleum ether was poured in to wash 3 times, and then transferred to a Buchner funnel for vacuum filtration for 10 min to obtain immobilized lipase based on pure carboxymethyl chitosan microspheres.
[0076] Comparative Example 2 In order to compare the effect of lignin on the mechanical properties and enzyme activity of immobilized enzymes, immobilized lipase based on carboxymethyl chitosan / alkali lignin composite microspheres was prepared with reference to Example 1 when the alkali lignin was not modified: 0.05 g alkali lignin, 0.3 g carboxymethyl chitosan, and 0.12 g of Candida rugosa lipase were dissolved in deionized water to prepare 10 g of aqueous solution; the aqueous solution was added to 100 g of liquid paraffin containing 1.0 wt% Span-80, and emulsified at 500 rpm for 30 min using mechanical stirring; 2.0 g of a cross-linking agent solution containing 50 mg EDC and 25 mg NHS was added dropwise to the obtained W / O emulsion, and the mixture was stirred for cross-linking for 2 h at room temperature. After the reaction was completed, the mixture was allowed to stand for 10 min to separate the layers, and the upper oil phase was poured out. 200 ml of a mixture containing 100 ml deionized water and 100 ml petroleum ether was poured into the mixture to wash three times. The mixture was then transferred to a Buchner funnel and vacuum filtered for 10 min to obtain immobilized lipase based on carboxymethyl chitosan / alkali lignin cross-linked composite microspheres.
[0077] Comparative Example 3 In order to compare the effect of lignin on the mechanical properties and enzyme activity of immobilized enzyme, in the case where alkali lignin was only aminated, immobilized lipase based on carboxymethyl chitosan / aminated lignin composite microspheres was prepared with reference to Example 1: 2.0 g alkali lignin was dissolved in 4.0 mol / L sodium hydroxide solution to prepare 10 g 20 wt% alkali lignin solution; 6.0 g 37 wt% formaldehyde aqueous solution and 2.0 g ethylenediamine were added under stirring, mixed evenly and heated to 80 ° C for 1 h to obtain an aminated lignin solution; the reacted solution was poured into a dialysis bag (1000 Da) and dialyzed for 5 days, and freeze-dried to obtain an aminated alkali lignin powder; 0.05 g aminated lignin, 0.3 g carboxymethyl chitosan, and 0.12 g of Candida rugosa lipase were dissolved in deionized water to prepare 10 g aqueous phase solution; the aqueous phase solution was added to 100 g containing 1.0 wt% In liquid paraffin of Span-80, mechanical stirring was used to emulsify at 500 rpm for 30 min; 2.0 g of a crosslinker solution containing 50 mg EDC and 25 mg NHS was added to the obtained W / O emulsion, and the mixture was stirred and crosslinked for 2 h at room temperature. After the reaction was completed, it was allowed to stand for 10 min to separate the layers, and the upper oil phase was poured out, and 200 ml of a mixed solution containing 100 ml deionized water and 100 ml petroleum ether was poured in to wash three times, and then transferred to a Buchner funnel and vacuum filtered for 10 min to obtain immobilized lipase based on carboxymethyl chitosan / aminated lignin crosslinked composite microspheres.
[0078] Example effect description: The effect is mainly explained by taking Example 1 as an example.
[0079] Figure 1is the infrared spectrum of alkali lignin and modified lignin prepared in Example 1, 1612 cm -1 、1506cm -1 It is the characteristic peak of the skeleton of lignin benzene ring, 1705cm -1 The C=O stretching vibration peak of the carboxyl group is 3280 cm -1 The 1705m -1 The carboxyl C=O stretching vibration peak disappears at 1601cm -1 A broad peak appeared at 1650 cm-1, which may be because the carboxylate exists in the form of carboxylate after the reaction, and the stretching vibration peak of the carboxyl group shifts to the short-wave band, which is different from the peak at 1650 cm-1. -1 At the same time, after chemical modification, 1460cm -1 The CN stretching vibration peak of the amine group is enhanced, 1406cm -1 The in-plane bending vibration peak of the hydroxyl group on the carboxyl group was enhanced, indicating that the carboxyl functional group was introduced while increasing the content of the amine functional group on the alkali lignin.
[0080] from Figure 2 and Figure 3 The SEM image of the immobilized lipase based on carboxymethyl chitosan / lignin cross-linked composite microspheres prepared in Example 1 shows that the immobilized enzyme is in the shape of a regular sphere, and the surface of the microspheres is smooth and non-porous; after drying, the interior does not collapse and is also a non-porous structure.
[0081] In order to explore whether the carboxymethyl chitosan / lignin cross-linked composite microspheres prepared in Example 1 were loaded with lipase, the loaded lipase was labeled with fluorescein isothiocyanate (FITC) and laser confocal detection was performed at an excitation wavelength of 490 nm. Figure 4 This is a laser confocal microscope photo of the immobilized lipase composite microspheres. It can be seen that the green fluorescent lipase is distributed on the composite microspheres, while no green fluorescence appears where there are no composite microspheres, indicating that the lipase has been successfully loaded on the composite microspheres.
[0082] The immobilized lipase based on carboxymethyl chitosan / lignin cross-linked composite microspheres in Example 1 and the pure carboxymethyl chitosan microspheres in Comparative Example 1 were placed in an oven at 60°C for 24 hours, dried, ground into powder and pressed into thin slices. 5 μL of deionized water was dropped on the thin slices using a contact angle meter. The larger the contact angle, the more hydrophobic the material. Figure 5 It can be seen that the contact angle of carboxymethyl chitosan microspheres is 43.9°, and the contact angle of carboxymethyl chitosan / lignin cross-linked composite microspheres is 54.5°, indicating that the incorporation of modified lignin improves the hydrophobicity of carboxymethyl chitosan microspheres immobilized lipase.
[0083] The force required for the immobilized lipase microspheres prepared in the examples and comparative examples to break was measured using a texture analyzer. The greater the force required, the better the mechanical properties of the microspheres. Texture analyzer test parameters: test type - compression, 10 microspheres were compressed at the same time, compression deformation target was 30%, trigger point load was 0.005N, and test speed was 2mm / min.
[0084] Olive oil hydrolysis was selected as a model reaction to determine the catalytic performance and recyclability of the immobilized lipase prepared in the examples and comparative examples. The specific operations are as follows: ① Prepare substrate: 2% (w / v) polyvinyl alcohol solution, mix with olive oil in a volume ratio of 3:1, and homogenize for 15 minutes at 11000rpm in a homogenizer; ② Take 2ml Tris-HCl buffer and 0.1g immobilized enzyme and mix them evenly, shake at 37℃ and 150rpm for 10 minutes, add 2.5ml substrate and continue to shake at 37℃ and 150rpm for 30 minutes, then use a 100-mesh screen to sieve out the immobilized enzyme microspheres, and add 4ml of anhydrous ethanol to the remaining liquid to terminate the reaction; ③ Potentiometric titration: Use 0.05mol / L sodium hydroxide to titrate the remaining liquid with the anhydrous ethanol mixture to determine the amount of fatty acids in the olive oil hydrolysis product, and then calculate the catalytic activity of the lipase. The enzyme activity unit is defined as: the amount of enzyme required to hydrolyze olive oil to release 1.0 μmol of fatty acid per minute at 37°C is 1 enzyme activity unit (U). The enzyme activity is calculated according to the following formula: E: enzyme activity, U / mg; V 样品 : Volume of sodium hydroxide used in the sample, ml; V 空白 : Volume of sodium hydroxide used for blank, ml; C NaOH : The concentration of sodium hydroxide used for titration is 0.05 mol / L; t: reaction time, min; m: mass of immobilized enzyme, mg.
[0085] The immobilized enzyme microspheres screened out were washed three times with buffer (pH = 8.0) and their catalytic activity was measured again. This process was repeated 7 times, and the initial enzyme activity of the first reaction was set as 100% to calculate the relative enzyme activity.
[0086] Figure 6The mechanical properties and enzyme activity of the immobilized lipase obtained in Examples 1 to 7 and Comparative Examples 1 to 3. It can be seen from the figure that the enzyme activity and crushing force of Comparative Example 2 are slightly higher than those of Comparative Example 1, indicating that the rigid polycyclic aromatic hydrocarbon structure of lignin can enhance the mechanical properties of the microspheres, and its hydrophobicity can improve the enzyme activity. The enzyme activity and crushing force of Comparative Example 3 are higher than those of Comparative Example 2, indicating that although alkaline lignin can improve the catalytic activity of immobilized lipase and enhance the mechanical properties of microspheres, it is not as effective as the aminated lignin in improving the enzyme activity and mechanical properties. This is because alkaline lignin is insoluble in water and cannot be evenly dispersed in the aqueous solution, and is unevenly distributed in the microspheres; while the water solubility of the aminated modified lignin is enhanced, and the lignin has a group that can be cross-linked, so that the gel microspheres formed are more cross-linked, and less lipase falls during the washing process.
[0087] The enzyme activities of Examples 1 to 7 were 1.56-1.88 U / mg, and the crushing forces were 1.55-3.55 N, both higher than those of Comparative Example 3, which proves that the covalent bonding degree of the modified lignin by amination and then carboxylation of the present invention with carboxymethyl chitosan and lipase is higher, and the mechanical properties and enzyme activity of the microspheres can be further improved.
[0088] 10g of immobilized lipase based on carboxymethyl chitosan / lignin cross-linked composite microspheres of Example 1 and pure carboxymethyl chitosan microspheres of Comparative Example 1 were added to 20ml of deionized water, and the turbidity of the suspension was measured by a turbidimeter after magnetic stirring at 800rpm to explore the effect of lignin introduction on the mechanical properties of microsphere immobilized enzyme. The higher the turbidity of the suspension, the more the microspheres are broken and the weaker the mechanical strength. Figure 7 The turbidity of the suspension after stirring the microspheres for different times. It can be seen that the turbidity of the composite microspheres after stirring for 8, 16, and 24 hours is about half of the turbidity of the carboxymethyl chitosan microspheres, indicating that the composite microspheres are less broken. It also shows that the incorporation of lignin significantly improves the mechanical properties of the microspheres.
[0089] Figure 8 The reusability of the immobilized lipase prepared in Example 1 and the immobilized lipase of pure carboxymethyl chitosan microspheres in Comparative Example 1. After 7 cycles of use, the immobilized lipase in Example 1 had 90.5% of its enzyme activity remaining, while the immobilized lipase of pure carboxymethyl chitosan microspheres had only 73.6% of its enzyme activity remaining. The composite microspheres exhibited better reusability due to the introduction of lignin, because the incorporation of lignin increased the cross-linking degree and mechanical strength of the gel network, reduced the drop of lipase due to leakage and sphere breakage during use, and thus increased its activity retention rate during recycling.
[0090] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing immobilized lipase based on carboxymethyl chitosan / lignin cross-linked composite microspheres, characterized in that: The following steps are involved: (1) dissolving lignin in an alkaline solution, adding formaldehyde and an amination modifier to carry out an amination reaction to obtain aminated lignin; then adding an amino coupling agent and a carboxylation modifier to carry out a carboxylation reaction, dialyzing, and drying to obtain aminated-carboxylation modified lignin; (2) mixing carboxymethyl chitosan, aminated-carboxylated modified lignin, lipase and water to obtain an aqueous phase solution; mixing the aqueous phase solution and an oil phase containing a surfactant, emulsifying, and obtaining a W / O emulsion; (3) Adding an amino coupling agent solution dropwise to the W / O emulsion to undergo a cross-linking reaction at room temperature, allowing the emulsion to stand for stratification, removing the lower layer, washing it, and filtering it to obtain immobilized lipase based on carboxymethyl chitosan / lignin cross-linked composite microspheres.
2. The preparation method according to claim 1, characterized in that: The mass ratio of lignin, formaldehyde and aminated modifier in step (1) is 1: (0.37-1.11): (0.2-1.0); The lignin in step (1) is at least one of alkali lignin, enzymatic lignin and lignin sulfonate; The amination modifier in step (1) is at least one of ethylenediamine, diethylenetriamine, triethylenetetramine and tetraethylenepentamine; The carboxyl modifier in step (1) is at least one of ethylenediaminetetraacetic acid and diethylenetriaminepentaacetic acid; The amino coupling agent in step (1) is 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide; The mass ratio of the lignin, the amino coupling agent and the carboxyl modifier in step (1) is 1: (0.12-0.8): (0.5-2.0).
3. The preparation method according to claim 2, characterized in that: The amount of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide is 100-400 mg / g lignin, and the amount of N-hydroxysuccinimide is 0.2-1.0 mg / mg 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide; the mass ratio of the lignin to the carboxyl modifier is 1:(0.5-2.0); The mass ratio of the lignin, formaldehyde and aminated modifier is 1: (0.555-1.11): (0.2-1.0); The mass ratio of the lignin, the amino coupling agent and the carboxyl modifier is 1: (0.15-0.2): (0.5-2.0).
4. The preparation method according to claim 1, characterized in that: In step (2), the mass of the carboxymethyl chitosan accounts for 3.0 to 9.0 wt % of the aqueous solution; the mass of the aminated-carboxylated modified lignin accounts for 0.5 to 9.0 wt % of the aqueous solution; The dosage of the lipase in step (2) is 0.05-0.8 g / g carboxymethyl chitosan; In the surfactant-containing oil phase of step (2), the surfactant content is 0.5-3.0 wt%; The mass ratio of the aqueous phase solution to the oil phase containing the surfactant in step (2) is 1:2 to 1:10; The lipase in step (2) is at least one of Candida rugosa lipase, Aspergillus niger lipase and Candida albicans lipase; The surfactant-containing oil phase in step (2) is at least one of liquid paraffin, ethyl acetate, dodecane and soybean oil; In the surfactant-containing oil phase of step (2), the surfactant is at least one of Span-80, Span-60, sucrose ester, Tween-80, sodium dodecyl sulfate and sodium dodecylbenzene sulfonate.
5. The preparation method according to claim 4, characterized in that: The mass of the carboxymethyl chitosan accounts for 3.0-6 wt % of the aqueous solution; the mass of the aminated-carboxylated modified lignin accounts for 0.5-5 wt % of the aqueous solution; The dosage of the lipase is 0.4-0.6 g / g carboxymethyl chitosan; The surfactant content in the surfactant-containing oil phase is 1.0 to 2.0 wt %; The mass ratio of the aqueous phase solution to the oil phase is 1:8 to 1:
10.
6. The preparation method according to claim 1, characterized in that: The amino coupling agent in the amino coupling agent solution of step (3) is 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and N-hydroxysuccinimide; the amount of the amino coupling agent solution is 10-30 wt% of the aqueous phase solution; the concentration of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide in the amino coupling agent solution is 2.5-25 wt%, and the amount of N-hydroxysuccinimide is 0.2-1.0 mg / mg 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide; The cross-linking reaction time in step (3) is 1 to 6 hours.
7. The preparation method according to claim 1, characterized in that: The temperature of the amination reaction in step (1) is 60-90°C, and the reaction time is 1-4 h; The temperature of the carboxylation reaction in step (1) is 30-40°C and the time is 12-36 hours; The emulsification speed in step (2) is 100 to 800 rpm, and the time is 10 to 120 min.
8. The preparation method according to claim 1, characterized in that: In step (1), the alkaline solution is at least one of a sodium hydroxide solution and a potassium hydroxide solution, and the concentration of the alkaline solution is 1.0 to 4.0 mol / L; the concentration of the lignin in the alkaline solution is 20 to 60 wt%; In step (1), the formaldehyde is added in the form of a formaldehyde solution, and the concentration of the formaldehyde solution is 30-40 wt%.
9. The immobilized lipase prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the immobilized lipase according to claim 9.
Citation Information
Cited By
Method for in-situ encapsulation of enzyme by using lignin
CN120118896A
Hydrogel adsorbent as well as preparation method and application thereof
CN121892107A